THE FOREIGN DIRECT INVESTMENTS AND THE LABOUR MARKETS FROM DEVELOPING COUNTRIES - Diaconu (Maxim) Laura (Annals of the University of Oradea: Economic Science, 2016)
More powerful tools are available, for multidimensional analysis, through which data can be more efficiently used, both at the strategic and technical levels.